Lirik Lagu Sawfa Nabqa Huna: Telaah Teks Analisis Wacana Kritis Teun Van Dijk - Miftahul Ilmi; Syofyan Hadi; Wartiman Wartiman (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
This article analyzed the lyrics of the Sawfa Nabqa Huna song composed by Adil Masyithi as a form of resistance to Moammar Ghodafi who ruled Libya at that time. The main focus of this research was the choice of words and how the composition of the lyrics of this song was composed by Adil Masyithi to convey the message to the listeners. The data in this study were analyzed using Teun A. Van Dijk's critical discourse analysis model. Some words used by Adil Masyithi which contain the core message in the lyrics of the song Sawfa Nabqa Huna are the words ???? and ???. The composer saw that every wound and pain must be healed with medicine (????), including wounds that afflict Libya. The word pen (???) referred to studying because intelligent people are not easily influenced by any party. Pen (???) was also interpreted by writing, one of the media that can be used to convey aspirations.